Potentilla fulgens root extract's effect on breast cancer (MCF-7) and osteosarcoma (U2OS) cells proliferation and migration (Annals of Medical Research, 2024)
Aim: This study evaluates the cytotoxic effect of Potentilla fulgens root extract on MCF-7, U2OS, and RPE-1 cell lines and investigates its impact on cell migration.Material and Methods: The effect of Potentilla fulgens root extract on the cell viability of MCF-7, U2OS, and RPE-1 cells was analyzed using an MTT assay. The effect of the compounds on cell migration was evaluated at 24 and 48 hours using the wound healing assay. A wound-healing assay was used to measure the metastatic ability of cells in vitro.Results: MTT assay showed that PRE had a cytotoxic effect on all three cell lines, depending on dose and time, and this effect was statistically significant. The wound healing assay results showed that PRE slowed the migration of live MCF-7 and U2OS cancer cells, and these effects increased over time.Conclusion: As a result, this study indicates that PRE may be very useful in treating human osteosarcoma and breast cancer.